2021
DOI: 10.5194/acp-2021-707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redistribution of total reactive nitrogen in the lowermost Arctic stratosphere during the cold winter 2015/2016

Abstract: Abstract. During winter 2015/2016 the Arctic stratosphere was characterized by extraordinarily low temperatures in connection with the occurrence of extensive polar stratospheric clouds. From mid of December 2015 until mid of March 2016 the German research aircraft HALO (High Altitude and Long–Range Research Aircraft) was deployed to probe the lowermost stratosphere in the Arctic region within the POLSTRACC (Polar Stratosphere in a Changing Climate) mission. More than twenty flights have been conducted out of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The campaign was based in Kiruna (67.5 • N, 20.3 • E), Sweden, and spanned the boreal winter-spring season from 17 December 2015 to 18 March 2016 with 18 science flights and 156 flight hours. The campaign accommodated a number of different science goals, including trace gas composition in the upper troposphere and lower stratosphere (Marsing et al, 2019;Johansson et al, 2019;Braun et al, 2019;Keber et al, 2020;Ziereis et al, 2022), gravity waves (Krisch et al, 2020) and polar stratospheric clouds (Voigt et al, 2018). Therefore, the flight strategy often needed to avoid extended sections in cirrus clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The campaign was based in Kiruna (67.5 • N, 20.3 • E), Sweden, and spanned the boreal winter-spring season from 17 December 2015 to 18 March 2016 with 18 science flights and 156 flight hours. The campaign accommodated a number of different science goals, including trace gas composition in the upper troposphere and lower stratosphere (Marsing et al, 2019;Johansson et al, 2019;Braun et al, 2019;Keber et al, 2020;Ziereis et al, 2022), gravity waves (Krisch et al, 2020) and polar stratospheric clouds (Voigt et al, 2018). Therefore, the flight strategy often needed to avoid extended sections in cirrus clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nitric acid distribution shows a local maximum at and below flight altitude from ∼ 15:00 to ∼ 17:00 UTC. As discussed by Ziereis et al (2021), during this flight nitrified air masses were observed in situ at flight altitude during the first leg and the last leg, while descended denitrified air masses were observed at flight altitude during the central part of the flight. The local maximum in the GLORIA HNO 3 distribution below flight altitude between about 15:00 and 17:00 UTC is interpreted as subsided nitri- As shown in Fig.…”
Section: Trace Gas Distributionsmentioning
confidence: 56%
“…12c clearly shows that this species is enhanced in the simulation by ∼ 1 to 1.5 ppbv in large parts of the LMS as a consequence of nitrification by evaporated HNO 3 -containing particles that sedimented from polar stratospheric clouds. In the middle of the flight, air masses that are affected by HNO 3 depletion reach into the LMS and are the consequence of subsidence of denitrified air masses in the polar vortex (see Khosrawi et al, 2017, andZiereis et al, 2021). Above flight altitude, sequestration of HNO 3 on existing PSC particles might still play a role under sufficiently cold conditions.…”
Section: Quantification Of Model Discrepancies and Sensitivity Studiesmentioning
confidence: 99%